Assessment of piezometric distribution and vulnerability of groundwater to pollution in a tropical environment: the case study of the aquifer of Santchou, Cameroon, Central Africa - Nkembe, Silfried Ewoukem; Defo, Célestin (Sustainable water resources management, 2022)
The alluvial groundwater table in the city of Santchou constitutes the main source of water supply for the consumption of the population. However, it is increasingly subject to pollution pressures mainly from agricultural activities and from intense and anarchic urbanization. The main objective of this study was to protect and prevent the pollution of groundwater resources in the alluvial plain of Santchou (West Cameroon) through the analysis of its susceptibility to surface pollution. More specifically, it was a question of evaluating the piezometric of this aquifer, analyzing and mapping its intrinsic vulnerability to pollution using the DRASTIC method. Water level monitoring campaigns were therefore carried out in 70 wells sampled in the study area; direct observations, digital terrain models and digital elevation models were used to characterize the soil, the unsaturated layer (USL) and the aquifer medium. The Williams and Kissel equation coupled with water balance was used for the assessment of aquifer recharge, while that of Porchet was used for the assessment of the permeability of the aquifer. MS Excel software and GIS Arcgis 10.2 software were used in the processing and analysis of data. The results obtained showed an average variation of the piezometry of 2.5 m from low water period to high water period, with a uniform behavior in the progression. Four vulnerability classes were established in the study area, with a predominance of very high vulnerability class (50% of the study area). It was observed that topographic slope (with 95% of the study area dominated by slopes of between 0 and 2%), the unsaturated layer (with thicknesses varying from 0.1 to 4.5 m) and the aquifer recharge (182.7 mm/year) played a major role as parameters influencing groundwater vulnerability in the study area. This groundwater, the main means of supplying water to households in the locality, are therefore vulnerable to surface pollution, and the need of improving the sanitation conditions in this locality is essential for its security. The integration of this specificity in the choice of decisions to redevelop the local urban space will make it possible to guarantee better security of the groundwater resource.